Câu a: Rút gọn biểu thức P
P = [(2x√x + x - √x) / (√x³ - 1)] - [(x + √x) / (x - 1)] * [(x - 1) / (2x√x - √x + 2√x - 1)] + √x / (2√x - 1)
= [(x√x + √x + x - √x) / (√x - 1)(x + √x + 1)] - [(x + √x) / (2√x - 1)(√x + 1)] + √x / (2√x - 1)
= [x(√x + 1) / (√x - 1)(x + √x + 1)] - [√x(√x + 1) / (2√x - 1)(√x + 1)] + √x / (2√x - 1)
= [x / (√x - 1)(x + √x + 1)] - [√x / (2√x - 1)] + √x / (2√x - 1)
= [x / (√x - 1)(x + √x + 1)]
Vậy P = x / (√x - 1)(x + √x + 1).
Câu b:
Áp dụng bất đẳng thức Cauchy-Schwarz, ta có:
(1/a(a+b) + 1/b(a+b))^2 ≤ [(1/a)^2 + (1/b)^2][(a+b)^2 + (a+b)^2]
⇔ 1/a(a+b) + 1/b(a+b) ≤ √[(a^2 + b^2) / (a^2b^2)] * √[2(a+b)^2]
⇔ 1/a(a+b) + 1/b(a+b) ≤ √[(a+b)^2 / (a^2b^2)] * √2
⇔ 1/a(a+b) + 1/b(a+b) ≤ (a+b) / (ab) * √2
Vì a + b ≤ 1 nên:
1/a(a+b) + 1/b(a+b) ≤ √2
Mà √2 < 4, do đó:
1/a(a+b) + 1/b(a+b) < 4
Vậy bất đẳng thức được chứng minh.
Xem thêm (+)